Early outcomes of alcohol septal ablation for hypertrophic obstructive cardiomyopathy: a European multicenter and multinational study - Veselka, Josef; Lawrenz, Thorsten; Stellbrink, Christoph; Zemanek, David; Branny, Marian; Januska, Jaroslav; Sitar, Jan; Dimitrow, Pawel; Krejci, Jan; Dabrowski, Maciej; Mizera, Stanislav; Bartel, Thomas; et al. (Catheterization and cardiovascular interventions, 2014)
BACKGROUND: This study was designed to evaluate the outcomes of alcohol septal ablation (ASA) under multicenter and multinational conditions. METHODS: Data for 459 patients (age 57 ± 13 years) from nine European centers were prospectively collected and retrospectively analyzed. RESULTS: ASA led to a significant reduction in outflow gradient (PG) and dyspnea [median of PG from 88 (58-123) mm Hg to 21 (11-41) mm Hg; median of NYHA class from 3 (2-3) to 1 (1-2); P < 0.01]. The incidence of 3-month major adverse events (death, electrical cardioversion for tachyarrhythmias, resuscitation) and mortality was 2.8% and 0.7%, respectively. Permanent pacemakers for post-ASA complete heart block were implanted in 43 patients (9%). Multivariate analysis identified higher amount of alcohol (however, in generally low-dose procedures), higher baseline left ventricular ejection fraction and higher age as independent predictors of PG decrease ≥50%. CONCLUSIONS: The results of the first European multicenter and multinational study demonstrate that real-world early outcomes of ASA patients are better than was reported in observations from the first decade after ASA introduction.
Keywords: senioři; Heart Septum; ethanol; senioři nad 80 let; hypertrofická kardiomyopatie; Retrospective Studies; Europe; Time Factors; výsledek terapie; Evropa; srdeční septum; Ethanol; Middle Aged; mužské pohlaví; alcohol septal ablation; míra přežití; funkce levé komory srdeční; mladý dospělý; Adult; Cardiac Surgical Procedures; Cardiomyopathy, Hypertrophic; Follow-Up Studies; ablace; následné studie; Aged, 80 and over; Young Adult; hypertrophic cardiomyopathy; ženské pohlaví; retrospektivní studie; kardiochirurgické výkony; Humans; Survival Rate; časové faktory; cardiomyopathy; lidé středního věku; Ablation Techniques; dospělí; Female; Aged; Treatment Outcome; lidé; Male; Ventricular Function, Left